Pengaruh Ukuran Perusahaan, Usia Perusahaan, Leverage, Profitabilitas, Struktur Kepemilikan Saham, Investasi, Peluang Investasi terhadap Dividen, Free Cash Flow - Darmawan, Ari (Universitas Brawijaya, Indonesia, 2011)
The research is aimed at examining the role played by dividend to reduce free cash flow (FCF) in the company, as stated in the free cash flow hypothesis. Research also examines the factors affecting the dividend and FCF Population of research includes all go public manufacturing companies which were listed at Indonesia Stock Exchange in period 2004-2008. Research sample is 126 companies. Research provides the evidence that the companies which are willing to pay for dividend are those about to reduce their FCF. The characteristic of companies with dividend payment, or with lower FCF. includes: (a) a long existence in the industry. (b) lower leverage, (c) high managerial stock ownership. (d) low institutional stock ownership, (e) high investment fund, and high growth opportunity.